ANALISIS KENDALA DAN EFEKTIVITAS PENERAPAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) KEUANGAN PADA DINAS PRKPP KABUPATEN BARITO UTARA KALTENG - Indah Dirza Lestari; M. Zainal Abidin (Administraus, 2022)
ABSTRACT : The purpose of this study was to analyze the constraints and effectiveness of implementing SIMDA Finance at the PRKPP Office of North Barito Regency, Central of Borneo. This study uses a case study method with a descriptive qualitative approach. This survey research intends to analyze the phenomenon of the constraints and Effectiveness of the Implementation of the Regional Management Information System (SIMDA) in Finance. The 5 (five) dimensions of effectiveness measurement used in this study are based on the opinion of Campbell, J. P. consisting of the dimensions of program success, target success, program satisfaction, input and output levels, and overall goal achievement. The results of this study indicate that there are several obstacles in the implementation of the SIMDA Finance application that need to be improved, including the absence of documentation regarding the summary flow chart that shows the data cash flow/flow, and the lack of comprehensive data integration between SIMDA Finance. and SIMDA BMD between financial reporting and asset reporting. There are still several data input operators (users) of Financial SIMDA who do not understand the financial report cycle, resulting in data input errors and need to improve data input, the capacity of SIMDA Finance's computer server still needs to be upgraded (upgrade), there is still no Electric Generator and lack of Computer UPS which can support the Financial SIMDA Application Server remains on in the event of a power outage and maintenance (maintenance) The Financial SIMDA application is also still dependent on the task force team of the Financial and Development Supervisory Agency (BPKP). Meanwhile, when viewed from the effectiveness of the Implementation of the Financial SIMDA Application based on the dimensions of the effectiveness of the application of the Financial SIMDA, it shows very effective results in 3 (two) dimensions of Effectiveness, namely program success, target success, and overall goal achievement, but on 2 (two) other dimensions, namely Satisfaction with the Program. and the input-output level only shows effective results. ABSTRAK : Tujuan penelitian ini adalah untuk menganalsis kendala-kendala dan efektifitas penerapan SIMDA Keuangan pada Dinas PRKPP Kabupaten Barito Utara Kalimantan Tengah. Penelitian ini menggunakan metode studi kasus dengan pendekatan kualitatif deskriptif. Penelitian survei ini bermaksud untuk menganalisis fenomena tentang kendala dan Efektivitas Penerapan Sistem Informasi Manajemen Daerah (SIMDA) Keuangan. 5 (lima) Dimensi pengukuran efektivitas yang digunakan dalam penelitian ini berdasarkan pendapat Campbell, J. P. terdiri dari dimensi keberhasilan program, keberhasilan sasaran, kepuasan terhadap program, tingkat input dan output, dan pencapaian tujuan menyeluruh. Hasil penelitian menunjukkan ada beberapa kendala-kendala dalam penerapan aplikasi SIMDA Keuangan yang perlu diperbaiki, antara lain adalah belum ada dokumentasi mengenai bagan arus ringkasan (summary flow chart) yang memperlihatkan aliran/arus kas data, belum terintegrasinya data secara menyeluruh antara SIMDA Keuangan dan SIMDA BMD antara pelaporan keuangan dan pelaporan asset. masih adanya beberapa operator input data (user) SIMDA Keuangan yang belum memahami siklus laporan keuangan sehingga mengakibatkan kesalahan input data dan perlu perbaikan input data, kapasitas kemampuan server komputer SIMDA Keuangan masih perlu ditingkatkan (upgrade), masih belum adanya Genset Listrik dan kurangnya UPS Komputer yang bisa mendukung Server Aplikasi SIMDA Keuangan tetap menyala bila terjadi adanya pemadaman listrik serta perawatan (maintenance) Aplikasi SIMDA Keuangan juga masih menggantungkan diri kepada tim satuan tugas Badan Pengawasan Keuangan dan Pembangunan (BPKP). Sedangkan jika dilihat dari efektifitas Penerapan Aplikasi SIMDA Keuangan berdasarkan dimensi efektifitas penerapan SIMDA Keuangan menunjukan hasil sangat efektif pada 3 (dua) dimensi Efektifitas yaitu keberhasilan program, keberhasilan sasaran, dan pencapaian tujuan menyeluruh, namun pada 2 (dua) dimensi lainnya yaitu Kepuasan terhadap Program dan tingkat input-output hanya menunjukkan hasil efektif.